(3GdHMK GdYdej aj GOGQI GdGYeGd HGSJNOGe JbfjGJ GdMGShHs - (3LdGd eMeO(B, (3GdfYjejs ((3YeGf(B:s (3OGQ GKQGA(B,s, 2008)
(3GdHMK GdYdej aj EOGQI GdCYeGd , fXe GdeYdheGJ hGOGQI GdeYQaI ,GdYde hGdfXQjI hGdHMK GdYej , GSJQGJLjI GdHMK GdYdej aj GOGQI GdGYeGd , YedjI GdHMK GdYdej , eTcdI GdHMK hebJQMg , GdHjGfGJ , RSGFd LeY GdeYdheGJ hGdHjGfGJ , GdYjfGJ , YQV GdHjGfGJ , JfXje hJQejR hJMdjd GdHjGfGJ , GSJNOGe GdMGShH aj GONGd hJMdjd GdHjGfGJ , GSJNOGe GdTHcI GdeYdheGJjI aj GdMUhd Ydi GdHjGfGJ , cJGHI JbQjQ GdHMK s
(3HjHdjhZQGajG U(B.291-296s
Keywords: (3GOGQI GdGYeGds; (3GdMGShHs; (3HMK Ydejs